Should doctors intentionally do less than the best? - Savulescu, J (1999)
The papers of Burley and Harris, and Draper and Chadwick, in this issue, raise a problem: what should doctors do when patients request an option which is not the best available? This commentary argues that doctors have a duty to offer that option which will result in the individual affected by that choice enjoying the highest level of wellbeing. Doctors can deviate from this duty and submaximise--bring about an outcome that is less than the best--only if there are good reasons to do so. The desire to have a child which is genetically related provides little, if any, reason to submaximise. The implication for cloning, preimplantation diagnosis and embryo transfer is that doctors should only produce a clone or transfer embryos expected to enjoy a level of wellbeing which is less than that enjoyed by other children the couple could have, if there is a good reason to employ that technology. This paper sketches what might constitute a good reason to submaximise.